2007
DOI: 10.1097/01.scs.0000249359.56417.7e
|View full text |Cite
|
Sign up to set email alerts
|

Complex Orbito-fronto-temporal Reconstruction Using Computer-Designed PEEK Implant

Abstract: Cosmetic and functional reconstruction of large and complex calvarial defects remains a challenge for craniofacial surgeons. Computer-designed alloplastic implants have revolutionized the conceptualization and approach to these reconstructions and have become a reliable and irreplaceable part of the surgical armamentarium. We are reporting a case of complex orbito-fronto-temporal reconstruction using a computer-designed PEEK (polyetheretherketones)-Patient Specific Implant (PSI). To the best of our knowledge, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
90
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(92 citation statements)
references
References 11 publications
0
90
0
2
Order By: Relevance
“…3 In a series of 29 patients, not a single CFRP plate had to be removed. 39 The CAD/CAM PEEK implants for cranioplasty are gaining access in calvarial reconstruction, 42 but larger case studies have not yet been reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…3 In a series of 29 patients, not a single CFRP plate had to be removed. 39 The CAD/CAM PEEK implants for cranioplasty are gaining access in calvarial reconstruction, 42 but larger case studies have not yet been reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10] Reports of the use of PEEK in the reconstruction of maxillofacial defects have been limited. 11 However, we believe that PEEK-coupled with a prefabrication process that can produce patient-specific implants (PSIs)-may represent an ideal strategy in the reconstruction of challenging maxillofacial defects. In addition, because PEEK implants are durable, workable, and biocompatible, the use of the implant may become more popular in the future.…”
mentioning
confidence: 99%
“…The core driving factor to the development of PEEK as a biomaterial was the need to balance strength and rigidity: to develop an implant system which met the structural strength requirements of the body, whilst minimizing rigidity in an attempt to reduce stress shielding risk [33,81]. Traditionally PEEK found use in spinal treatment applications, as well as cranial and maxillofacial applications [54,56,82]. It must be noted that PEEK is a hydrophobic material.…”
Section: Discussionmentioning
confidence: 99%